2016
DOI: 10.1186/s11671-016-1735-8
|View full text |Cite
|
Sign up to set email alerts
|

Atom Diffusion and Evaporation of Free-Ended Amorphous SiOx Nanowires: Nanocurvature Effect and Beam-Induced Athermal Activation Effect

Abstract: Arresting effects of nanocurvature and electron beam-induced athermal activation on the structure changes at nanoscale of free-ended amorphous SiOx nanowire were demonstrated. It was observed that under in situ uniform electron beam irradiation in transmission electron microscope, the near surface atoms at the most curved free end of the nanowire preferentially vaporized or diffused to the less curved wire sidewall. The processing resulted in an intriguing axial shrinkage and an abnormal radial expansion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The phase diagram can be divided into four parts. Part I indicates the deformation of SiO 2 under low-dose irradiation, which has been discussed in other works [23, 24]. Parts II and III represent the formation of amorphous SiO x and crystalline Si NPs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The phase diagram can be divided into four parts. Part I indicates the deformation of SiO 2 under low-dose irradiation, which has been discussed in other works [23, 24]. Parts II and III represent the formation of amorphous SiO x and crystalline Si NPs.…”
Section: Resultsmentioning
confidence: 88%
“…The images in Figure 1(b1)–1(b3) are high magnification TEM images revealing the changes in the surface from curved to flat and then to curved again as the irradiation dose increased at 25°C. The former process indicates the deformation of SiO 2 , which is attributed to beam-induced athermal activation of massive plastic flow and surface migration [23, 24]. The latter process is the formation of amorphous SiO x NPs due to the desorption of O.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, as we have mentioned above, the fact that the evolution will stop immediately once the irradiation is suspended also demonstrates an ultrafast irradiation-induced athermal activation effect. In fact, our previous research [6,[8][9][10][11] has demonstrated that our proposed novel nanocurvature effect and energetic beam-induced athermal activation effect are universal phenomena and applicable in prediction or explanation of nanophenomena of LDNs. In the following, we attempt to reveal the above two effects on the reshapings of a-SiOx NW especially the axially curved a-SiOx NW under a uniform e-beam irradiation.…”
Section: Resultsmentioning
confidence: 94%
“…In fact, our previous work on the energetic beam irradiation-induced structural instabilities and processing of low dimensional nanostructures (LDNs), such as nanocavities in Si [16,[28][29][30][31], carbon nanotubes [32,33] and amorphous SiOx nanowires [22,34], has proven that our proposed nanocurvature effect [16,17] and energetic beam-induced athermal activation effect [16,18] For the nanocurvature effect on a nanowire, we can suppose that, similar to the particle case [16,17], when the diameter of a nanowire reduces down to nanoscale and can be comparable to its atomic bond length, a positive nanocurvature on the highly curved wire surface will become appreciable, as shown in Fig. 3(a).…”
Section: Resultsmentioning
confidence: 99%